Legal measures regarding the operation of agricultural cooperatives : An International Comparative Study - Sarnnoi , Egkapong; Chadit, Chumnan (Journal of Humanities and Social Sciences Loei Rajabhat University, 2024)
This research aimed to study consider and consider the provisions of laws, rules, regulations and measures under the Cooperative Act B.E. 2542 of Thailand and abroad. and comparative analysis of legal measures regarding the operations of agricultural cooperatives in Thailand and abroad. Using in-depth interviews of a sample group. By conducting in-depth interviews with 10 cooperative officials from the Cooperative Promotion Office in Bangkok. The results from studying foreign laws and from in-depth interviews revealed that the Cooperatives Act of 1999 imposes restrictions on the operations of agricultural cooperatives. The provisions of the 1999 Cooperative Act contain measures by which the state exercises power over cooperatives. Although cooperative regulations are a guideline for operations, they are under close supervision by the registrar. while foreign law An important policy of the government is not to interfere in the operations of cooperatives and to try to reduce the role of controlling cooperatives so that cooperatives can conduct business independently. Therefore, current measures that affect the operations of agricultural cooperatives That should be amended include the Cooperative Act B.E. 2542 of Thailand, amending Section 33, specifying the form of cooperatives according to the business model, especially savings cooperatives and agricultural cooperatives, and Section 33/1 regarding the qualifications of associate members. According to the announcement of the Cooperative Registrar regarding the relationship of associate members with the cooperative or cooperative members. As a result, agricultural cooperatives are unable to accept farmers outside their operating boundaries as associate members according to the cooperative’s existing regulations.